STATE OF THE COMMERCIAL ICHTHYOFAUNA OF MAIBALYK LAKE (AKMOLA REGION, KAZAKHSTAN) (Experimental biology, 2022)
Study of resources of commercial fish of local water bodies and description of peculiarities of their population structure is an actual research.The purpose of the work was to determine hydrochemical parameters, modern species composition of commercial ichthyofauna, size and weight and age structure of fish, as well as the features of the distribution of fish species in the water area of the reservoir on the example of Lake Maibalyk.The drainless lake Maibalyk is located between the rivers Nura and Ishim, and is included in the list of fishery reservoirs of local importance of Akmola region.  The research was conducted in June 2021. Hydrochemical indicators (oxygen, pH, nitrate, nitrite) and population structure of commercial fish and their distribution (interpolation) were studied by conventional hydrochemical, ichthyological and modern methods as QGIS.To determine the population structure, we used a scientific net of mesh size 20-70 mm. According to the results 8 commercial fish species were recorded in Lake Maibalyk: roach, bream, tench, carp, crucian carp, perch, ruff and pike. The dominant species in the lake are roach, bream, crucian carp and perch. The other species are rare, and pike were only found in recreational catches by fishermen. The vast majority of the age composition of commercial fish was younger, from 2 to 4 years old.
Keywords: Maybalyk lake, ichthyofauna, commercial fish species, age composition, population.